Inside cyber warfare - Carr, Jeffrey; Shepherd, Lewis (Sebastopol, Calif. : O'Reilly Media, Inc., 2010)
'You may have heard about'cyber warfare' in the news, but do you really know what it is? This book provides fascinating and disturbing details on how nations, groups, and individuals throughout the world are using the Internet as an attack platform to gain military, political, and economic advantages over their adversaries. You'll learn how sophisticated hackers working on behalf of states or organized crime patiently play a high-stakes game that could target anyone, regardless of affiliation or nationality. Inside Cyber Warfare goes beyond the headlines of attention-grabbing DDoS attacks and takes a deep look inside multiple cyber-conflicts that occurred from 2002 through summer 2009. Learn how cyber attacks are waged in open conflicts, including recent hostilities between Russia and Georgia, and Israel and Palestine; discover why Twitter, Facebook, LiveJournal, Vkontakte, and other sites on the social web are mined by the intelligence services of many nations; read about China's commitment to penetrate the networks of its technologically superior adversaries as a matter of national survival; find out why many attacks originate from servers in the United States, and who's responsible; and, learn how hackers are'weaponizing' malware to attack vulnerabilities at the application level'--Back cover.
'Mapping the cyber underworld'--Cover.
Includes index.
Keywords: Computer crimes; Cyberterrorism; Information warfare; Terrorism